Current Status of Research, Regulations, and Future Challenges for CRISPR Gene-Editing in Crop Improvement - Sadikshya Sharma; Seonghee Lee; Heqiang Huo (EDIS)
Recently, new plant-breeding technology such as CRISPR gene editing has provided the potential to substantially improve crop breeding in agriculture. Considerable efforts have been devoted to apply this gene-editing technology in modern agriculture to increase crop yields and improve the quality of food ingredients, especially by many of the major agronomic seed-producing companies. In this new 4-page article, we outline the recent research updates and regulations on gene editing in crop improvement. Written by Sadikshya Sharma, Heqiang Huo, and Seonghee Lee and published by the UF/IFAS Horticultural Sciences Department. https://edis.ifas.ufl.edu/hs1334